Expanding the limits of vaginal surgery: Transvaginal vesicolithotomy for an incarcerated procidentia: A case report and literature review - Themistoklis Mikos; Nikolaos Roussos; Iakovos Theodoulidis; Grigoris F. Grimbizis (Elsevier, 2024)
Bladder stones are rare in women. This report presents the case of a woman with a massive bladder stone and incarcerated procidentia. The 75-year-old woman presented to the outpatient clinic with procidentia and recurrent urinary tract infections. Preoperative imaging led to the diagnosis of cystolithiasis. After multidisciplinary counseling the patient underwent a vaginal hysterectomy with bilateral oophorectomy and transvaginal vesicolithotomy. A bladder biopsy was performed to rule out any malignancy. After three days, the patient was discharged with a Foley catheter; 15 days later, the bladder catheter was removed. She had an uncomplicated postoperative course. The presence of cystolithiasis and pelvic organ prolapse remains a challenge both in diagnosis and in treatment. The literature lacks solid evidence on the optimal management of these cases. Although there are no recommendations or consensus for their treatment, it seems that the one-step vaginal approach is preferable to the abdominal route.